Prognostic factors for overall survival and safety of trans-arterial chemoembolization (TACE) with irinotecan-loaded drug-eluting beads (DEBIRI) in patients with colorectal liver metastases - Šljivić, Maja (Radiology and oncology (Ljubljana), 2024)
Transarterial chemoembolisation with irinotecan-loaded drug-eluting beads (DEBIRI TACE) can be considered in patients with unresectable colorectal cancer liver metastases (CRLM) who progress after all approved standard therapies or in patients unsuitable for systemic therapy. Patients and methods Between September 2010 and March 2020, thirty patients (22 men and 8 women; mean age 66.8 ± 13.2) were included in this retrospective study. DEBIRI TACE was conducted in 43% of patients unsuitable for systemic therapy as a first-line treatment and 57% as salvage therapy after the progression of systemic therapy. All the patients had liver-limited disease. In the case of unilobar disease, two treatments were performed at four-week intervals, and in the case of bilobar disease, four treatments were performed at two-week intervals. All patients were premedicated and monitored after the procedure. Adverse events were graded according to the Cardiovascular and Interventional Radiological Society of Europe (CIRSE) classification system for complications. Results The median overall survival (OS) from the beginning of DEBIRI TACE in the salvage group was 17.4 months; in the group without prior systemic therapy, it was 21.6 months. The median overall survival of all patients was 17.4 months (95% confidence interval CI: 10.0–24.7 months), and progression-free survival (PFS) was 4.2 months (95% CI: 0.9–7.4 months). The one-year survival rate after the procedure was 61%, and the two-year rate was 25%. Univariate analysis showed better survival of patients with four or fewer liver metastases (p = 0.002). There were no treatment-related deaths or grade 4 and 5 adverse events. Nonserious adverse events (Grades 1 and 2) were present in 53% of patients, and Grade 3 adverse events were present in 6% of the patients. Conclusions DEBIRI TACE is a well-tolerated treatment option for patients with liver metastases of colorectal cancer. Patients with four or fewer liver metastases correlated with better survival.
Keywords: imrinotekan; kolorektalni rak; metastaze v jetrih; transarterijska kemoembolizacija